Force-velocity characteristics of upper limb extension during maximal wheelchair sprinting performed by healthy able-bodied females - Hintzy, F.; Predine, E.; Rouillon, J. D.; Belli, A. (Journal of Sports Sciences, 2003)
The aim of this study was to determine the relationship between force and velocity parameters during a specific multi-articular upper limb movement--namely, hand rim propulsion on a wheelchair ergometer. Seventeen healthy able-bodied females performed nine maximal sprints of 8 s duration with friction torques varying from 0 to 4 N x m. The wheelchair ergometer system allows measurement of forces exerted on the wheels and linear velocity of the wheel at 100 Hz. These data were averaged for the duration of each arm cycle. Peak force and the corresponding maximal velocity were determined during three consecutive arm cycles for each sprint condition. Individual force-velocity relationships were established for peak force and velocity using data for the nine sprints. In line with the results of previous studies on leg cycling or arm cranking, the force-velocity relationship was linear in all participants (r = -0.798 to -0.983, P < 0.01). The maximal power output (mean 1.28 W x kg(-1)) and the corresponding optimal velocity (1.49 m x s(-1)) and optimal force (52.3 N) calculated from the individual force-velocity regression were comparable with values reported in the literature during 20 or 30 s wheelchair sprints, but lower than those obtained during maximal arm cranking. A positive linear relationship (r = 0.678, P < 0.01) was found between maximal power and optimal velocity. Our findings suggest that although absolute values of force, velocity and power depend on the type of movement, the force-velocity relationship obtained in multi-articular limb action is similar to that obtained in wheelchair locomotion, cycling and arm cranking.